A voice from the Holocaust - Soumerai, Eve Nussbaum; Schulz, Carol D. 1948- (Voices of twentieth century conflict, 2003)
Eve Sounmerai recounts her childhood as a Jewish girl growing up in Nazi Berlin, as a teenaged refugee in the United Kingdom, and later as a young adult searching for answers in postwar Germany.